800 Years of Making: Early Medieval Craftworking and an 8th-Century Decline in Ireland. Issue 2 (3rd July 2021) - Hannah, Emma
Abstract : METHODOLOGICAL ADVANCES IN STATISTICAL MODELLING of chronological data have enabled fresh perspectives of the past to be gained from the analysis of large numbers of radiocarbon ( 14 C) dates. A new analysis of radiocarbon dates associated with craftworking activities — handicrafts like antler-working or wood-working and metalworking technologies — from Irish sites of early medieval date is presented using a bootstrapped kernel density estimation (KDE) method. These models are used to assess whether the arrival of urbanism to Ireland in the 10th century brought about a major change to craftworking traditions, and to build a new and nuanced understanding of long-term trends at both secular and ecclesiastical sites of the period. These are shown to have differed, especially in the 8th century, at a crucial point in time. The findings add to the emerging narrative of demographic 'decline' from similar data-driven investigations of Ireland's early medieval past, which pinpoint the beginning of the 8th century as a seminal moment of change. Crucially, however, they also reveal a more complex pattern of change involving a combination of processes, independent of urban development, but related to demographics, socio-economic re-organisation, changing settlement patterns, and the influence of the Church.